Leveraging in vivo animal models of tendon loading to inform tissue engineering approaches - Muscat, Samantha; Nichols, Anne E. C. (Frontiers in Bioengineering and Biotechnology, 2024)
Tendon injuries disrupt successful transmission of force between muscle and bone, resulting in reduced mobility, increased pain, and significantly reduced quality of life for affected patients. There are currently no targeted treatments to improve tendon healing beyond conservative methods such as rest and physical therapy. Tissue engineering approaches hold great promise for designing instructive biomaterials that could improve tendon healing or for generating replacement graft tissue. More recently, engineered microphysiological systems to model tendon injuries have been used to identify therapeutic targets. Despite these advances, current tissue engineering efforts that aim to regenerate, replace, or model injured tendons have largely failed due in large part to a lack of understanding of how the mechanical environment of the tendon influences tissue homeostasis and how altered mechanical loading can promote or prevent disease progression. This review article draws inspiration from what is known about tendon loading from in vivo animal models and identifies key metrics that can be used to benchmark success in tissue engineering applications. Finally, we highlight important challenges and opportunities for the field of tendon tissue engineering that should be taken into consideration in designing engineered platforms to understand or improve tendon healing.